Parental Speech at 6 Months Predicts Joint Attention at 12 Months. (13th April 2013) - Roberts, Siwan; Fyfield, Rhiannon; Baibazarova, Eugenia; van Goozen, Stephanie; Culling, John F.; Hay, Dale F.
Abstract : In a prospective longitudinal study of a representative community sample ( N  = 264), mothers' references to infants' mental states were coded during a topic‐sharing task in the home at 6 months. Joint attention behaviour was assessed in the laboratory at 12 months. Individual joint attention skills (gaze following, gaze alternating, and declarative pointing) were significantly inter‐correlated, with a single factor accounting for 68% of the variance. Mothers' references to infants' mental states at 6 months predicted infants' joint attention at 12 months. The association was not explained by sociodemographic characteristics of the family, the mother's mental state, or by the quantity or acoustic properties of her speech. However, variability in pitch of maternal speech was an independent predictor of the infants' later joint attention skills. Taken together, these findings suggest that mothers' infant‐directed speech fosters infants' attentive participation in topic‐sharing interactions, which in turn provide an important arena in which joint attention skills develop over the first year of life.